Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw dengan Crossword Puzzle terhadap Hasil Belajar Biologi - Siska Arimadona (Eduscience Development Journal, 2019)
This research originated from observation in the field that most of the students under the KKM. This situation is thought to occur because the teacher is still learning to use a variety of learning models, motivation and interest in learning of students whom are still lacking. This study aimed to determine the effect of class VIII student learning outcomes in the subjects of biology at SMP N 1 Kecamatant Lareh Sago Halaban in plant material motion using cooperative learning model with a crossword puzzle jigsaw. Based on the results of this study concluded that the learning outcomes Biology students use cooperative learning model crossword puzzle jigsaw with effect on in the learning outcomes of student against class VIII in motion material plant in SMPN 1 Kecamatan Lareh Sago Halaban